2021
DOI: 10.1002/mmce.22956
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic olefin copolymer‐based copper clad laminate and the application for low loss broadband baluns

Abstract: In this article, a novel copper clad laminate based on cyclic olefin copolymer (COC) is proposed and manufactured by using lamination process. The loss characteristic of manufactured laminate is investigated by comparing the measured results of two microstrips on proposed COC‐based laminate and traditional Rogers RT/duroid 5880, respectively. Moreover, the SIW/HMSIW baluns operated at X‐band are designed on the proposed laminate, and the measured results verify the inherent out‐of‐phase performance and good am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Finally, plasma‐treated LCP and oxidized copper coated with functionalized agent were laminated at 180°C to obtain the final sample. The peel test results showed that the peeling strength of the sample reached 8.92 N cm −1 , which met the standard for industrial application 28,29 …”
Section: Introductionmentioning
confidence: 65%
“…Finally, plasma‐treated LCP and oxidized copper coated with functionalized agent were laminated at 180°C to obtain the final sample. The peel test results showed that the peeling strength of the sample reached 8.92 N cm −1 , which met the standard for industrial application 28,29 …”
Section: Introductionmentioning
confidence: 65%
“…11 Cyclo-olefin polymers (COPs) are gaining attention as low Dk polymers. 12 A representative commercial COP, such as ZEONOR (Zeon Corporation), is synthesized from ringopening polymerization of norbornenes, which generate a lowpolarity cyclopentane ring in the polymer main chain. As a result, COPs have a Dk of 2.3, significantly superior to those of epoxy and aromatic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Among olefins, cyclic olefin copolymer (COC) has an ultra-low D k of 2.21 and an ultra-low D f of 0.00021 at 10 GHz. Therefore, blending COC with PB would be an effective method to reduce the D f of the substrates [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%